2023
DOI: 10.1093/evlett/qrad010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting evolution in experimental range expansions of an aquatic model system

Abstract: Predicting range expansion dynamics is an important goal of both fundamental and applied research in conservation and global change biology. However, this is challenging if ecological and evolutionary processes occur on the same time scale. Using the freshwater ciliate Paramecium caudatum, we combined experimental evolution and mathematical modeling to assess the predictability of evolutionary change during range expansions. In the experiment, we followed ecological dynamics and trait evolution in independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Recent studies have highlighted that rapid evolution can complicate our ability to predict the ecoevolutionary dynamics of range expansions (Miller et al 2020;Shaw et al 2023;Williams et al 2019;Zilio et al 2023). Here, we used replicate range-expanding populations to empirically test whether the presence of selection from an abiotic gradient across landscapes could modify the among-replicate variability, and hence predictability, of range expansion speed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted that rapid evolution can complicate our ability to predict the ecoevolutionary dynamics of range expansions (Miller et al 2020;Shaw et al 2023;Williams et al 2019;Zilio et al 2023). Here, we used replicate range-expanding populations to empirically test whether the presence of selection from an abiotic gradient across landscapes could modify the among-replicate variability, and hence predictability, of range expansion speed.…”
Section: Discussionmentioning
confidence: 99%
“…We see three main ways to improve integration between conceptual theory, modelling and evolution experiments. First, modelling and experimental evolution can be strengthened by mutually informing each study design—tailored experiments can validate analytical or statistical models, aid in model selection or evaluate predictability (Zilio et al, 2023; Figure 1, arrow 3 and 4). For example, theory has shown that high levels of genetic polymorphism in dispersal traits and/or high mutation rates can accelerate range expansion and alter trade‐offs between reproductive output and movement/dispersal capacity (Elliott & Cornell, 2012; Morris et al, 2019).…”
Section: Further Advancing the Field: Linking Theory Experimental Evo...mentioning
confidence: 99%